A Systematic Review: Comparison between result of USG Examination and FNAB Examination in Breast Tumors - Dalilah Badzlin (Jurnal KESANS : Kesehatan dan Sains, 2023)
Introduction: Cancer is a type of disease non-infectious which the incidence rate has trend of increasing every year WHO data in 2010 mentioned that cancer ranks number two as the cause most deaths, are under the disease cardiovascular. More than 80% of breast cancer cases in Indonesia was diagnosed at an advanced stage so the morbidity and mortality rates become higher.  Ultrasonography (USG) of the breast generally used for inspection example cyst breast, and the shape of the cyst for breast abnormalities. FNAB is a fine needle biopsy examination and is a preoperative diagnostic tool for breast lesions. Anatomical histopathology is the gold standard for the diagnosis of breast malignancy. Objective: To find out the differences and compare the results of breast tumor examination using ultrasound and FNAB examination Method: This study uses a type of literature review study a Narrative Review design. The method used in the process of using the ultrasound, it can be seen that the gray scale ultrasound examination has a sensitivity of 75-94.4% and a specificity of 18.8-81.8%. Result and Discussion: While PPV 48-95.6%, NPV 42.8-95.7%, and 46.9% accuracy and fine needle examination also has varying accuracy criteria. Its show a sensitivity of 86.7%- 93,4% Specificity 95,7% -100%. Conclusion: Fine Needle Aspiration examination has better specitifity than ultrasound examination.